Assessment of an alternative accounting and analytical system or individual entrepreneurs - T. M. Nepryahina (Вестник университета)
The growth of individual entrepreneurs annually creates a special layer of small businesses, however, both legally and practically, the existing accounting systems do not consider the specifics of such a business, therefore, the search for an alternative accounting system is an urgent problem. The purpose of this study is to evaluate the previously proposed alternative integrated accounting and analytical system for individual entrepreneurs by creating a test to assess the requirements for organizing accounting and analytical systems by individual entrepreneurs, assess the elements of the management system in the proposed integrated system, and assess the processing of accounting information by three types of systems: traditional, functional and integrated. The study used a systematic method, as well as methods of analysis, synthesis, comparison. Based on the results of the study, a conclusion was made about the advantage of an alternative accounting and analytical system for individual entrepreneurs in comparison with the existing traditional accounting system. The results of the study can become the basis for improving the proposed early alternative integrated accounting and analytical system for individual entrepreneurs and can be used as state recommendations for keeping records by individual entrepreneurs, as well as introducing the accounting system structure into new alternative enterprise resource planning systems.